Financing Donor Projects: trends, challenges and opportunities - Agyemang, Rebecca (2021)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology. Kumasi in partial fulfilment of the requirement for the award degree of Master of Science in Project Management,